Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1128/aem.61.4.1614-1619.1995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of uptake and hydrolysis of fluorescein diacetate and carboxyfluorescein diacetate by intracellular esterases in Saccharomyces cerevisiae, which result in accumulation of fluorescent product

Abstract: Flow cytometry is a rapid and sensitive method which may be used for the detection of microorganisms in foods and drinks. A key requirement for this method is a sufficient fluorescence staining of the target cells. The mechanism of staining of the yeast Saccharomyces cerevisiae by fluorescein diacetate (FDA) and 5-(and 6-)carboxyfluorescein diacetate (cFDA) was studied in detail. The uptake rate of the prefluorochromes increased in direct proportion to the concentration and was not saturable, which suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(122 citation statements)
references
References 26 publications
4
116
1
1
Order By: Relevance
“…It has previously been demonstrated that after passive diffusion into hepatocytes, the nonfluorescent CDFDA is rapidly hydrolyzed by intracellular esterases to the fluorescent dye CDF, which is subsequently actively transported into the canalicular compartments by Mrp2. 22,23 The overlay of confocal and transmission images of SCRH (Fig. 6) showed that CDF is indeed predominantly located in the canalicular networks after 15 min of incubation, confirming the functional activity of canalicular transport in SCRH.…”
Section: Biliary Excretion Of Taurocholate and Tauro-nor-thca-24-dbd mentioning
confidence: 54%
“…It has previously been demonstrated that after passive diffusion into hepatocytes, the nonfluorescent CDFDA is rapidly hydrolyzed by intracellular esterases to the fluorescent dye CDF, which is subsequently actively transported into the canalicular compartments by Mrp2. 22,23 The overlay of confocal and transmission images of SCRH (Fig. 6) showed that CDF is indeed predominantly located in the canalicular networks after 15 min of incubation, confirming the functional activity of canalicular transport in SCRH.…”
Section: Biliary Excretion Of Taurocholate and Tauro-nor-thca-24-dbd mentioning
confidence: 54%
“…For viability staining, cells were resuspended in phosphate-bu¡ered saline (PBS) containing 10 Wg ml 31 £uorescein diacetate (FDA) and 25 Wg ml 31 PI. FDA is taken up by live cells and converted to its £uorescent derivative £uorescein by cellular esterases [17]. PI is taken up by dead cells because of a loss of membrane impermeability [18].…”
Section: Fluorescence Stainingmentioning
confidence: 99%
“…More recently, flow cytometry has been applied to physiological studies with algae, bacteria, and yeasts. Examples include cell viability analysis using fluorescein diacetate (FDA) to measure esterase activity [8] and membrane potential analysis using the cationic dye 3,3Ј-dihexyloxacarbocyanine (DiOC 6 [3]) [9,10]. Flow cytometric techniques have important advantages over conventional biochemical assays, because cell functions can be quickly determined at conditions close to the in vivo state [9].…”
Section: Introductionmentioning
confidence: 99%